2024
DOI: 10.1186/s12885-024-11879-6
|View full text |Cite
|
Sign up to set email alerts
|

An update of clinical value of circulating tumor DNA in esophageal cancer: a systematic review and meta-analysis

Yaozhong Zhang,
Huazhen Du,
Na Wang
et al.

Abstract: Background Esophageal cancer (EC) is a deadly disease with limited therapeutic options. Although circulating tumor DNA (ctDNA) could be a promising tool in this regard, the availiable evidence is limited. We performed a systematic review and meta-analysis to summarize the clinical applicability of the next-generation sequencing (NGS) and droplet digital polymerase chain reaction (ddPCR) technology on the ctDNA detection of the EC and listed the current challenges. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
(76 reference statements)
0
1
0
Order By: Relevance
“…Three studies observed a significant difference in DFS/PFS between patients with high versus low levels of pre-treatment ctDNA [14,16,17,23]. Mazurek et al notably identified that patients who were ctHPV16 DNA-positive prior to treatment had a better survival outcome versus patients who were ctHPV16-negative [18].…”
Section: Discussionmentioning
confidence: 99%
“…Three studies observed a significant difference in DFS/PFS between patients with high versus low levels of pre-treatment ctDNA [14,16,17,23]. Mazurek et al notably identified that patients who were ctHPV16 DNA-positive prior to treatment had a better survival outcome versus patients who were ctHPV16-negative [18].…”
Section: Discussionmentioning
confidence: 99%